Storage of Dendrocalamus strictus Nees, Seed for Maintenance of Viability and Vigour - Gupta, B. N.; Sood, O. P. (Indian Forester, 1978)
°Dendrocalamus strictus flowers and fruits gregariously at intervals of 20 to 40 years. It's Seed retain their viability for a period of about one year only, and suitable methods of storage to prolong their viability is not known. The present study has brought out that Dendrocalamus strictus seed can be stored with advantage over silica gel or anhydrous Calcium chloride in desiccator or at 3°C to 5°C ambient temperature after reducing the seed Moisture content to 8%. A seed lot with 67% germination capacity stored under the above conditions exhibited 51, 54 and 59% germination respetively after 34 months study has also indicated the presence of after-ripening in the seed which is overcome by storage under favourable conditions.